Exploring the digital extremist ecosystem: a preliminary analysis of hateful posts on Mod DB - Schlegel, Linda; Wiegold, Lars; Winkler, Constantin; Junk, Julian (Frontiers in Psychology, 2025)
The last 4 years have seen a stark increase in research on extremist activities in digital gaming spaces, particularly on gaming- and gaming-adjacent platforms. However, one area that has not received much attention so far are mod forums. While a large number of mods with hateful content have been created over the last two decades, the forums used to disseminate and discuss such mods have not yet been examined by extremism researchers. Considering the popularity of modding and mod forums among gaming communities, this is a crucial gap in our current understanding of extremist activities in digital gaming spaces. In an effort to address this research gap, this article offers an exploratory analysis of hateful and extremist posts on the popular mod forum Mod DB, including right-wing extremist, jihadist, antisemitic and mixed-ideology content. We seek to provide a preliminary glimpse into this under-researched digital space, complementing existing research on extremist activities on other gaming (−adjacent) platforms. Our research thereby broadens the current state of knowledge regarding the various gaming-related platforms frequented by extremist actors and radicalized individuals and contributes new insights about a thus far under-explored digital space.